Genetic screening of α-thalassemia fusion gene using routine flow-through hybridization - Huang, Yingbei; Ju, Aiping; Zheng, Lihong; Xu, Biqiu; Liang, Liang; Li, Youqiong (Frontiers in Genetics, 2024)
ObjectiveThe fusion gene is a rare form of α-thalassemia. Patients carrying the fusion gene could be misdiagnosed as normal or -α4.2deletion by the conventional thalassemia detection methods. The aim of this study was to present the detection of fusion genes using routine flow-through hybridization, as well as to analyze hematological and molecular characteristics.MethodsSamples were collected at our hospital from January 2019 to January 2024. Common thalassemia mutations in the Chinese population were conducted by flow-through hybridization. Samples showing faint coloration at the -α4.2 mutation site on hybridization membrane were considered suspicious. Samples detected as suspicious for -α4.2deletion were rechecked by conventional Gap-PCR. Those samples suspected of having -α4.2deletions were finally confirmed with specific primers for Gap-PCR and Sanger sequencing.ResultsOf the 32,083 samples, 25 samples (0.08%) were detected as suspected of having -α4.2 deletion by flow-through hybridization. However, upon reevaluation wtih conventional Gap-PCR reagents capable of detecting -α4.2 deletion, all were found to be negative for the deletion. Specific primers for Gap-PCR were designed, and fusion gene fragments were amplified. DNA sequencing of the HBA gene showed a 7-base mutation corresponding to the α-thalassemia fusion gene. Among the 25 samples, 22 were heterozygous carriers. Three samples were combined: one with Hb QS, one with β-thalassemia, and one with Hb G-Honolulu.Most hematological indices and capillary electrophoresis results were in the normal reference range.ConclusionThe fusion gene was present in 0.08% of the population in the Guangzhou region of Guangdong province, southern China. Conventional genetic methods tend to misdiagnose the fusion gene but can be effectively screened with flow-through hybridization.